2019
DOI: 10.1039/c9ra04481g
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering and antioxidative effects ofApium graveolensL. root flavonoid extracts

Abstract: Apium graveolens L. root flavone extract can improve hyperlipidemia induced by high-fat emulsion diet in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is rich in compounds including limonene, selinene, glycosides, flavonoids, and vitamins [11]. ese constituents are also reported to prevent cardiovascular diseases [12], jaundice [13], urinary tract obstruction [14], gout [15], and rheumatic disorders [16,17]. Celery seeds are spicy, carminative [18], diuretic [19], appetizer [20], stimulant, hypotensive [21], aphrodisiac, anti-inflammatory, and laxative [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is rich in compounds including limonene, selinene, glycosides, flavonoids, and vitamins [11]. ese constituents are also reported to prevent cardiovascular diseases [12], jaundice [13], urinary tract obstruction [14], gout [15], and rheumatic disorders [16,17]. Celery seeds are spicy, carminative [18], diuretic [19], appetizer [20], stimulant, hypotensive [21], aphrodisiac, anti-inflammatory, and laxative [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these drugs reduce the fatty acid synthesis and cellular fatty acid uptake. The previous studies reported that A. graveolence Lin seeds [28,29] Piperine [21] and vinegar [30,31] downregulate ACC, FAS. A. graveolence Lin seeds [29,32] Piperine, [21] P. anisum Lin seeds, [23] and A. cepa Lin bulb inhibits the activity of HMG-CoA reductase in animal models [26] A. cepa Lin bulb also inhibits lipogenic enzyme Glucose 6 phosphate dehydrogenase and malic enzyme.…”
Section: Discussionmentioning
confidence: 95%
“…The previous studies reported that A. graveolence Lin seeds [28,29] Piperine [21] and vinegar [30,31] downregulate ACC, FAS. A. graveolence Lin seeds [29,32] Piperine, [21] P. anisum Lin seeds, [23] and A. cepa Lin bulb inhibits the activity of HMG-CoA reductase in animal models [26] A. cepa Lin bulb also inhibits lipogenic enzyme Glucose 6 phosphate dehydrogenase and malic enzyme. [26] Suppression of ACC, FAS, [33] HMG-CoA reductase, [34] Glucose 6 phosphate dehydrogenase, and malic enzyme activity [35] reduces biosynthesis of endogenous lipids.…”
Section: Discussionmentioning
confidence: 95%
“…A reasonable explanation for this result is that the increase in temperature increased the solubility of the powders. After superfine pulverization, the particle size of the AR powders decreased, and their specific surface area substantially increase significantly, thereby exposing the hydrophilic groups of the powders and increasing the contact area with water (He, Shi, et al, 2019b). Therefore, the powders with a small particle size dissolved better in water than those with a large particle size, thereby improving the WSI of the AR powders.…”
Section: Resultsmentioning
confidence: 99%